Increase in Multidrug-resistant Tuberculosis (MDR-TB) in Alberta Among Foreign-born Persons: Implications for Tuberculosis Management - Long, Richard (Can J Public Health, 2013)
OBJECTIVES: Globally, the prevalence of anti-tuberculosis drug resistance has been increasing. This study sought to identify trends in multidrug-resistant tuberculosis (MDR-TB) among foreign-born persons in Alberta, a major immigrant-receiving province of Canada. METHODS: A retrospective cohort study design was used to investigate the prevalence of MDR-TB in foreign-born culture-positive TB cases between 1982 and 2011. Relevant demographic, clinical and laboratory data were abstracted from the TB Registry, individual medical records and the Provincial Laboratory for Public Health. RESULTS: Of the 2,234 foreign-born culture-positive TB cases in Alberta in 1982–2011, 27 (1.2%) had MDR-TB. Overall, MDR was associated with age <65 years (p=0.025), TB relapse/retreatment, and diagnosis and arrival in the last decade (2002–2011). The prevalence of MDR-TB in 2002–2011 was 2.1%, a significant increase from 0.65% in 1982–1991 (p=0.022) and 0.56% in 1992–2001 (p=0.009). Only immigrants from the Philippines and Vietnam showed a significant increase in the prevalence of MDR-TB between the first two decades and the last. Compared to MDR-TB cases reported in the first two decades, those reported in the last decade were more frequently younger than 35 years of age, new active versus relapse/retreatment cases and diagnosed with non-respiratory versus respiratory TB. In 1992–2011, MDR-TB strains had unique DNA fingerprints. CONCLUSIONS: Recent trends in the prevalence and clinical characteristics of foreign-born MDR-TB cases have important implications for TB case management in Canada. Early diagnosis of MDR-TB, using genotypic drug susceptibility testing, is suggested in foreign-born TB cases at increased risk of being MDR.